Measuring the Total Knowledge of English Sports Terminology by the Physical Education Students at Saudi Universities - Majed Saleem El-Saleh; Abdel Rahman Mitib Altakhaineh; Maher Madani Masoudi (The Society of Aging and Physical Activity (SAPA), 2019)
Background. Given the importance of English a global language and one of the four official languages used in FIFA, it is essential to acquaint students who are specialised in Physical Education with English sport terminology. Objectives. This study aims to determine the knowledge level of physical education students in Saudi universities' faculties and departments in relation to English sports terms. A survey was used to collect the relevant data from the participants. Methods. The study sample consisted of 600 students, who were selected using stratified random sampling during the academic year 2013-2014. The results indicate that the average percentage of correct answers was only 8.58%. Results. The results also suggest that there are statistically differences for study variables related to students' performance. Those students who actively play sports performed better than those who do not. Moreover, those students who have at least one non-Arab parent performed better than students who are of Arab parents. The researchers also found that graduates of international schools outperformed their private and public school peers. Finally, fourth year students achieved higher results than the more junior ones. Conclusion. The paper concludes with recommendations to review our language policy in general and to consider the addition of a unit or a chapter specific to English sports terminology in the curriculum to be taught to students in lectures. The researchers also recommend using and developing this test as a standard to determine the level of students' proficiency and the extent of their knowledge of English sports terminology.